Assembly of a β-(1 → 3)-glucan laminarihexaose on ionic liquid support. Issue 16 (19th April 2017) - Wang, Yanhui; Zhao, Xiaoke; Kong, Qiuyun; Yao, Jiajian; Meng, Xiangbao; Li, Zhongjun
Graphical abstract: Highlights: β-(1 → 3)-d -Glucan on ionic liquid (IL)-support was prepared with no chromatography required. IL-support laminarihexaose was rapidly assembled in 15 h with an average yield of over 90% per step. Combination of glycosylating agents were optimized by promoter, solvent, temperature. Abstract: An efficient method for the preparation of β-(1 → 3)-d -glucan laminarihexaose on ionic liquid (IL)-support is described. A β-(1 → 3)-glucan laminarihexaose was rapidly assembled in 15 h in a stereoselective fashion with an average yield of over 90% per step using an optimized combination of glycosylating agents. This ionic liquid support approach provides an efficient and fast means for the assembly of β-(1 → 3)-glucans.